Titik Café : Aplikasi Pencarian Café Menggunakan Metode Algoritma Ant Colony Kota Palangka Raya Berbasis Android - Perdana, Ravi; Lestari, Ariesta; Nugrahaningsih, Nahumi (Journal of Information Technology and Computer Science, 2022)
The increasing number of café in Palangka Raya makes people especially newcomers confused about choosing the right café to visit. In the end, sometimes people are stuck getting a cafe that is far from where they are, even though it turns out that there is a cafe they want that is close to them and also for newcomers to the city of Palangka Raya. This happens because currently, searching for cafes or restaurants is still limited to information from Google Maps only.Based on these problems, a system that can provide information is needed and is facilitated by finding the location of the café with the closest distance from the location of the application user. This study aims to build an android application that can display information and the location of a café that is presented in the form of an android application.This research applies the Ant Colony algorithm, as well as Google Maps and Mapbox as a digital map builder, and is developed based on Android. Making this application using the waterfall method, at the analysis stage the analysis stage is carried out on the things needed for making the application. At the design stage, program modeling is described in Data Flow Diagrams (DFD). Then at the coding stage of making this application using Android Studio, and testing this application using the black box method